A randomized controlled study comparing the efficacy of ultrasound guided intra articular-triamcinolone vs platelet rich plasma in active phase (stage 1) of adhesive capsulitis (frozen shoulder) - Thimmegowda, Darshan Gadenahalli; Ismail, Ihjas; P. V., Sharath Kumar (International Journal of Research in Orthopaedics, 2025)
Background: Adhesive capsulitis is a common cause of shoulder pain and restricted movement. Various treatment options exist, ranging from analgesics and steroid injections to biologics like platelet-rich plasma (PRP). PRP offers potential healing benefits with minimal immunological risk. Given conflicting evidence for existing therapies and the growing use of PRP, comparing PRP with steroid injections is warranted. Methods: A randomized, single-blinded controlled trial included 84 patients aged 30–70 years with adhesive capsulitis. Participants were randomized into Group A (triamcinolone 80 mg) and Group B (2 ml autologous PRP). Outcome measures included Visual Analogue Scale (VAS), range of motion (ROM), Shoulder Pain and Disability Index (SPADI), and Constant-Murley Score (CMS), assessed at baseline, 3 months, and 6 months. Statistical analysis employed Chi-square/Fisher’s exact test and Student’s t-tests. Results: Patients receiving PRP showed significantly greater improvements in VAS, SPADI, CMS, and ROM compared to those receiving steroid injections at both 3- and 6-month follow-ups (p<0.001). Transient side effects such as nausea, vomiting, and hypotension were more frequent in the PRP group but lacked statistical significance. Recurrence and lack of treatment response were higher in the steroid group. Conclusion: PRP is more effective than triamcinolone in short-term pain relief and functional recovery among adhesive capsulitis patients, with minimal adverse effects. Larger multi-centric studies with longer follow-up are recommended to evaluate its long-term benefits and comparative efficacy with other treatments.